Growth and Yield of Basmati Rice as Affected by Planting Date in Boro Season - Mannan, MA; Bhuiya, MSU; Akhand, MIM; Rana, MM; Zahan, A (Journal of Science Foundation, 2015)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The experiment was conducted at the Bangladesh Rice Research Institute Farm, Gazipur, in Boro season. BasmatiPNR, Basmati370, Basmati375 and Basmati-D were transplanted started from 10 December, and continued up to 25 January in the following year, at an interval of 15 days. Forty day old seedlings were transplanted spaced at 20 cm × 15 cm, to find out the optimum planting time and to select the Basmati varieties having high yield potential. The tallness of plants, number of tillers and dry matter were increased with the advancement of planting dates. On the country, number of panicles, grains panicle-1, panicle length, grain yield and growth duration decreased as delayed planting dates. The short stature BasmatiPNR and tall plant of Basmati375 exhibited higher number of panicles, grains panicle-1 and heavier individual grain which contributed to increase grain yield. Thus, high yield potential varieties BasmatiPNR and Basmati375 to be planted in optimum time on 10 December, to obtain maximum grain yield of rice in Boro season. DOI: http://dx.doi.org/10.3329/jsf.v11i2.21594 Journal of Science Foundation, 2013;11(2):37-42 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> <img src="data:image/png;base64,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